Transición del terrorismo al bioterrorismo como una amenaza para la supervivencia humana: reflexión bioética en el marco del bioderecho y la seguridad nacional (2021)
A bioethical reflection within the framework of biolaw and national security is a way to understand the transition from terrorism to bioterrorism as a threat to human survival, survival of the living and the ecosystem in all its manifestations. This reflection requires intertwining the life sciences with the humanities, in order to contribute to the epistemological construction of this threat, whose notion in the scientific literature lacks a legal definition, in the face of the multiplication of biological risks that especially affect Homo sapiens sapiens, around national security, human security and environmental security. The analysis presents, in a holistic manner, the impact of the bioterrorist threat at the global level, as well as for the Colombian State and the urgent need to regulate the use of biological weapons and agents in Colombia.